STRES KERJA, PENGARUHNYA TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI - Adawiyah, Robiatul; Siswanto, Siswanto (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2015)
The research aims to determine direct effect of work stress on employee perfor-mance, and job satisfaction as a mediating variable. This research was con-ducted at Islamic Banking in Malang. Explanatory research is used. Samplingtechnique used proportional random sampling with path analysis as dataanalysis. Research results showed the effect of work stress on employee perfor-mance was indirectly significant. While, the influence work stress on employeeperformance was not significant